Genome-wide analysis of transposable elements and satellite DNA in Humulus scandens, a dioecious plant with XX/XY1Y2 chromosomes - Zhang, Guo-Jun; Jia, Ke-Li; Wang, Jin; Gao, Wu-Jun; Li, Shu-Fen (Frontiers in Plant Science, 2023)
Transposable elements (TEs) and satellite DNAs, two major categories of repetitive sequences, are expected to accumulate in non-recombining genome regions, including sex-linked regions, and contribute to sex chromosome evolution. The dioecious plant, Humulus scandens, can be used for studying the evolution of the XX/XY1Y2 sex chromosomes. In this study, we thoroughly examined the repetitive components of male and female H. scandens using next-generation sequencing data followed by bioinformatics analysis and florescence in situ hybridization (FISH). The H. scandens genome has a high overall repetitive sequence composition, 68.30% in the female and 66.78% in the male genome, with abundant long terminal repeat (LTR) retrotransposons (RTs), including more Ty3/Gypsy than Ty1/Copia elements, particularly two Ty3/Gypsy lineages, Tekay and Retand. Most LTR-RT lineages were found dispersed across the chromosomes, though CRM and Athila elements were predominately found within the centromeres and the pericentromeric regions. The Athila elements also showed clearly higher FISH signal intensities in the Y1 and Y2 chromosomes than in the X or autosomes. Three novel satellite DNAs were specifically distributed in the centromeric and/or telomeric regions, with markedly different distributions on the X, Y1, and Y2 chromosomes. Combined with FISH using satellite DNAs to stain chromosomes during meiotic diakinesis, we determined the synapsis pattern and distinguish pseudoautosomal regions (PARs). The results indicate that the XY1Y2 sex chromosomes of H. scandens might have originated from a centric fission event. This study improves our understanding of the repetitive sequence organization of H. scandens genome and provides a basis for further analysis of their chromosome evolution process.